Implementasi Metode Fuzzy Logic Untuk Aplikasi Diagnosa Penyakit Pencernaan Manusia - Kurniawan, Harry; Gustientiedina; Desnelita, Yenny; Gusrianty (The Indonesian Journal of Computer Science, 2022)
The digestive system in humans is one of the vital organs of the body so that the health of the digestive system is very important to maintain. As a result, disseminating information regarding the diagnosis of human digestive disorders is critical in order to determine the sorts of diseases encountered by patients early on. The goal of this study is to design an application that uses an expert system and fuzzy logic to diagnose human digestive illnesses. This expert system can assist in the diagnosis of human digestive disorders and assist doctors in the diagnosis of human digestive diseases in patients. This expert system application uses the System Development Life Cycle (SDLC) for system development and uses the fuzzy logic approach to determine the severity of human digestive illnesses. Whereas, the Forward Chaining method is used for the tracing process that starts from the symptoms of the disease to produce answers to the types of human digestive diseases in the expert system. This research produces an expert system for diagnosing human digestive diseases based on the symptoms found using the fuzzy logic method.